Prediction Model of Academic Performance and Satisfaction With School According to Some Subjects of Compulsory Secondary Education - Baños, Raúl; Baena-Extremera, Antonio; Ortiz-Camacho, María del Mar (Psychological reports, 2020)
The purpose of the study was to know which subjects in the curriculum best predict school satisfaction and boredom as well as the student’s academic grade. The sample was of 680 adolescents of physical education (339 males, 341 females) with age between 12 and 18 years (M = 14.83; SD = 1.45). We used a questionnaire composed of the satisfaction scales with the subjects, intrinsic satisfaction in the school and related to academic grades. Descriptive analyses, correlations, and structural regression models were performed. The high levels of satisfaction and academic performance in physical education stand out. In the structural model, English is the subject that most predicts academic grades, while language predicts satisfaction at school and physical education boredom at it.